2017
DOI: 10.2147/coaya.s70375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial enrollment of adolescent and young adult patients with cancer: a systematic review of the literature and proposed solutions

Abstract: Abstract:Although there has been significant progress in the survival of children and older adults with cancer in the last few decades, this has not been the case for adolescent and young adults (AYAs). Although there are multiple reasons why outcomes for AYAs have not improved over time, it is evident from studies that AYAs fare better when enrolled in clinical trials, yet they are much less likely to participate in trials when compared with children and older adults. The goal of this review is to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…CCTs are an essential component for studying disease biology and improving survival and health‐related quality‐of‐life outcomes; however, only 3% to 14% of all AYAs with cancer enroll in a CCT . Previous reviews on this topic have identified patient‐level barriers to CCT enrollment, including concerns about treatment side effects and a lack of patient awareness . Our review has extended this body of literature to encompass site‐level barriers that may arise before the patient is ever presented with a CCT (eg, physician preference to present the trial) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CCTs are an essential component for studying disease biology and improving survival and health‐related quality‐of‐life outcomes; however, only 3% to 14% of all AYAs with cancer enroll in a CCT . Previous reviews on this topic have identified patient‐level barriers to CCT enrollment, including concerns about treatment side effects and a lack of patient awareness . Our review has extended this body of literature to encompass site‐level barriers that may arise before the patient is ever presented with a CCT (eg, physician preference to present the trial) .…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10,32 Previous reviews on this topic have identified patient-level barriers to CCT enrollment, including concerns about treatment side effects and a lack of patient awareness. 13,14 Our review has extended this body of literature to encompass sitelevel barriers that may arise before the patient is ever presented with a CCT (eg, physician preference to present the trial). 21 Despite a growing focus on AYA patients with cancer and disparities in care and outcomes, few studies have adequately addressed factors contributing to the low enrollment of AYAs into CCTs, and even fewer studies have assessed the efficacy of interventions enhancing AYA enrollment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AYA with cancer have lower improvements in survival rates than children and older adults and their low participation in cancer trials is believed to be a contributory factor [15][16][17]. This has prompted calls to identify and address barriers to trial enrolment in this age group [7,11].…”
Section: Introductionmentioning
confidence: 99%